Analysis of the level of physical fitness of cadets of theMilitary College of Sergeants of the National Academy of Land Forces in Lviv at the primary stage - Oderov, Artur; Kuznetsov, Maksym; Romanchuk, Serhii; Pohrebniak, Dmytro; Indyka, Svitlana; Bielikova, Nataliia (Jan Długosz University in Czestochowa, 2022)
Introduction: Providing troops with modern military equipment, technical means of transportationhas greatly facilitated the implementation of many elements of military activities by servicemen, but atthe same time contributed to some negative impact on their body and psyche, increased the need forgeneral and special physical training [2, 3]. The need for integrated use of physical education and sportsis well known and scientifically sound. The system of physical training of troops as a component of professional activity ensures the functioning of personnel in accordance with the requirements of physical fitness. Thus, the topical issue is to improve the content of physical training of cadets of military collegesof sergeants, taking into account the categories of servicemen. Purpose: Determining and improving the dynamics of general and special physical fitness ofcadets, taking into account the categories of servicemen. Results: A study of the level of physical fitness of cadets of the military college of sergeantsshowed that during the training of cadets in the first year indicators of general and special physical fitness have positive changes, but no significant difference was found (p  0.05).
Keywords: Military College of Sergeants of the National Academy of Land Forces in Lviv; Special Physical Training; Cadets; Armed Forces; General Physical Training; Physical Training